Technical Quality and Associated Iatrogenic Errors of Endodontic Treatments Performed in Extracted Anterior Single-Rooted Teeth by Preclinical Undergraduate Students - Dervenis Konstantinos; Koutroulis Andreas; Chatzopoulos Georgios; Kapralos Vasileios (Balkan Stomatological Society, 2015)
Aim: To evaluate technical quality of root canal treatments performed in extracted anterior single-rooted teeth in an undergraduate dental clinic, and to record the associated iatrogenic errors.